2013
DOI: 10.2174/18722105113079990004
|View full text |Cite
|
Sign up to set email alerts
|

Formulation Techniques for Nanofluids

Abstract: Fluids with suspended nanoparticles, commonly known as nanofluids, may be formulated to improve the thermal performance of industrial heat transfer systems and applications. Nanofluids may show enhanced thermal and electrical properties such as thermal conductivity, viscosity, heat transfer coefficient, dielectric strength, etc. However, stability problems may arise as nanoparticles usually have the tendency to agglomerate and sediment producing deterioration in the increment of these properties. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…The viscosity of nanofluid was predictable by using Redwood viscometer. It has been found that predominant in lower temperature range [65].…”
Section: Viscositymentioning
confidence: 93%
“…The viscosity of nanofluid was predictable by using Redwood viscometer. It has been found that predominant in lower temperature range [65].…”
Section: Viscositymentioning
confidence: 93%
“…Volume proportion and temperature impacts the property of viscosity of nano-fluids it turned into organized the usage of TiO 2 nano particle and measured the viscosity it's been discovered that viscosity of concentrated fluid will increase with the aid of including nanoparticles [23]. Viscosity of any discrete fluid turned into predicted via the use of redwood viscometer [24]. Experimental examines are conducted on Al 2 O 3 /R141b nano refrigerant, Lung Nodule Segmentation using Deep Learning and Advanced UNet Model measurement of the viscosity of nano fluid is carried out by employing using lvdv series viscometer [25].…”
Section: I S C O S I T Y O F N a N O F L U I D Smentioning
confidence: 99%